The effect of the assessment of practical-based work on pupils' problem solving and achievement in Basic Science and Technology in Odeda local government of Ogun State, Nigeria. Issue 6 (18th August 2019) - Omilani, Nathaniel A.; Akinyele, S. Akin; Durowoju, Tunde S.; Obideyi, Ebenezer Ifeoluw
ABSTRACT: Basic Science and Technology is a subject that is based on the broad field curriculum which is the foundation for science education in Nigeria at the basic level of education. Pupils learning outcomes is usually limited to the assessment of their achievement in paper pencil test. Pupils' skills in carrying out scientific investigation and the investigation they carry out is usually not assessed neither is the score part of pupils score in Basic Science and Technology. In this paper, we determined the effect of the integration of assessment of science practicals on basic four pupils' achievement and problem solving in Basic Science and Technology (basic science, basic technology, and information and communication technology). Participant 303 basic four pupils (primary four) in Odeda local government of Ogun. The result indicated that pupils in the treatment group were better problem solvers in two out of the three themes in Basic Science and Technology (basic science and basic technology). Also pupils in the treatment group had a significantly higher achievement in information and communication technology theme of Basic Science and Technology.